2020
DOI: 10.1002/mgg3.1378
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel splice mutation in SMAD3 in two Cypriot families with nonsyndromic thoracic aortic aneurysm. Two case reports

Abstract: Background Thoracic aortic aneurysm and dissection (TAA/D) represents a potentially lethal disease group characterized by an increased risk of dissection or rupture. Only a small percentage (approximately 30%) of individuals with nonsyndromic familial TAA/D have a pathogenic variant in one of the genes that have been found to be associated with the disease. Methods A targeted sequencing panel and direct sequencing approach were used to identify causative mutations in the index patients and other family members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Afterward, in silico analysis indicated that SMAD3 conformation was essential for the function of this protein and its interaction with other proteins. Smad family proteins are TFs binding to DNA sequences, and any changes and alterations may affect transcription 162 . Previous investigations have shown that the major portion of the candidate causal variants of SMAD3 is in the MH2 domain within exon 6 163 and that acceptor splice‐site variants usually result in proteins with impaired function 164 .…”
Section: Non‐coding Variants In Thoracic Aortic Aneurysms and Dissect...mentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, in silico analysis indicated that SMAD3 conformation was essential for the function of this protein and its interaction with other proteins. Smad family proteins are TFs binding to DNA sequences, and any changes and alterations may affect transcription 162 . Previous investigations have shown that the major portion of the candidate causal variants of SMAD3 is in the MH2 domain within exon 6 163 and that acceptor splice‐site variants usually result in proteins with impaired function 164 .…”
Section: Non‐coding Variants In Thoracic Aortic Aneurysms and Dissect...mentioning
confidence: 99%
“…Smad family proteins are TFs binding to DNA sequences, and any changes and alterations may affect transcription. 162 Previous investigations have shown that the major portion of the candidate causal variants of SMAD3 is in the MH2 domain within exon 6 163 and that acceptor splice-site variants usually result in proteins with impaired function. 164 In addition, Aubart et al 163 and Regalado et al 165 categorized loss-of-function variants located in SMAD3 as candidate causal ones.…”
Section: Non -Coding Variants In Thor Acic Aortic Aneurys Ms and Diss...mentioning
confidence: 99%
“…The most likely outcomes of alterations at acceptor (3′) or donor (5′) splice sites are exon skipping or cryptic splice site activation causing insertions, deletions, or intron retention [ 29 , 30 , 31 ]. Studies have demonstrated that an altered donor site could lead to skipping of the exon upstream the genetic change [ 32 , 33 , 34 ] as well as utilising the cryptic splice site upstream or downstream the canonical splicing site [ 35 , 36 , 37 ]. Moreover, a recent study by X. Lv et al revealed and further confirmed that a single variant in the canonical splicing site could induce production of several transcripts of different lengths and exonic/intronic structures.…”
Section: Discussionmentioning
confidence: 99%
“…LDS3 is characterized by aneurysms and tortuosity of the aorta and/or middle-sized arteries, accompanied by osteoarthritis (5,6). Currently, over 60 different P/LP variants in SMAD3 have been identified in LDS3 families (24)(25)(26)(27)(28), including missense, truncating and splicing variants, and intragenic and whole gene deletions (24,29,30). Interestingly, large phenotypic variation is described between LDS3 families, suggesting that, among others, genotype and ancestry might play a role.…”
Section: Introductionmentioning
confidence: 99%